Trial by fire and battle in medieval German literature - Ziegler, Vickie L. (Studies in German literature, linguistics, and culture., 2004)
Medieval judicial ordeals, especially trial by fire or battle, conjure up vivid pictures in the modern imagination. Yet popular perceptions of the Middle Ages leave the reader without a context in which to understand these most drastic of medieval judicial remedies. This book analyzes literary texts that provide some of the most vivid and detailed accounts of the medieval ordeal: the dramatic treason trials in late medieval Charlemagne epics. The two epics chosen - Stricker's 'Karl der Groe' and the 'Karlmeinet' - treat trial by battle as the living legal reality it was in those times, yet display very different attitudes toward feud and punishment in their respective (13th- and 14th-century) societies. Gottfried's 'Tristan' contains an ordeal by battle, of which the author approves, and an ordeal by fire, of which he does not, reflecting a common position of the intelligentsia of the time. Well after the condemnation of ordeals by the Fourth Lateran Council, the Kunigunde legend preserves the ordeal by fire much as it was portrayed in the mid-12th-century Richardis legend, while Stricker's short secular burlesque 'The Hot Iron, ' written in the mid 13th century, makes sport of this formerly serious legal proceeding, reflecting its sudden abandonment as a legal proof following the council's decision. The study brings extensive background material in legal and cultural history to bear on literary texts, helping both medievalists and general readers understand the function of the ordeal in the texts as well as in the larger society for whom these works were written. Vickie L. Ziegler is professor of German and Director of the Center for Medieval Studies at the Pennsylvania State University.